DETERMINING DOUBLE DEGREE STUDY PROGRAM THAT WILL BE OPEN CASE STUDY: MASTER OF BUSINESS ADMINISTRATION â MASTER OF SCIENCE IN INSTITUTE X - Anggraini, Diwita
The industrial revolution or known as industry 4.0 is a level of development in the industrial sector that has been digitized. Digitalization in most aspects of the industrial world is believed to increase the effectiveness and efficiency of a company. This has prompted many companies to digitize. This is directly proportional to the required human resources. Competence of human resources who must also improve and have knowledge related to science that has a concentration in electronic business, telecommunications with business, digital transformation and digital business. For this reason, research was made on the potential market share for concentration programs in business, telecommunications with business, digital transformation and digital business in order to know what actions to take. This research consists of 2 parts, the first part is exploratory research by holding focus group discussions and confirmative research using a descrete choice model. Analysis of this choice model is used to estimate the probability of respondents in the program offered. In this study, the author also designed a reference questionnaire using Ngene software. The results of the data from the ngene software are 16 scenarios which are divided into 4 types. After the authors get the related data, then proceed with data processing with multinominal logit (MNL) modeling techniques using software called Biogeme. The result of data processing using Biogeme software is the t test value which shows significant attributes and alternatives. From these results, the most significant alternative is digital business (2.5), without any significant attributes. For this reason, the program that can be opened is a digital business because it has the highest market potential among other programs.